ANALISIS PENGARUH LABELISASI HALAL, HARGA, PROMOSI, CITA RASA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SOSIS KANZLER OLEH GENERASI MILENIAL (STUDI PADA KONSUMEN SWALAYAN INDOMARET SRAGEN) - Atwal Arifin; Desy Setyaningrum (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Indonesia Digital Popular Brand Index survey concluded that Kanzler sausage is very popular with millennials because it is able to compete with 13 other well-known sausage brands. This study aims to analyze and look for empirical evidence regarding the effect of halal labeling, price, promotion, taste, and brand image on the purchasing decision of kanzler sausage by the millennial generation. This research is a quantitative research using primary data obtained from the distribution of questionnaires. The population in this research is Kanzler sausage consumers who are Indomaret Sragen customers. Samples were taken using the methodconvenience sampling.As well as multiple linear regression analysis techniques using the help of software SPSS 25. The results of this study found that the price and brand image variables had a partial effect on the purchasing decision of kanzler sausage by the millennial generation, while the halal labeling, promotion, and taste variables had no partial effect on the purchasing decision of kanzler sausage by the millennial generation.